Research on the Equilibrium of China’s Employment Structure (2015-2023): Industry, Population and Regional Dimensions - Zhou, Kun; Lu, Yuxim; Yu, Shuying; Yang, Wenyu (American Journal of Economics, 2026)
Purpose: The purpose of this study is to construct the equilibrium measurement system of China's employment structure and reveal its evolution law. Based on the three-dimensional framework of industry population region, this paper establishes comprehensive indicators, sorts out the dynamic trends driven by aging and industrial upgrading, identifies spatial differentiation and regional structural differences, and puts forward optimization policies. Materials and Methods: This study uses CRITIC objective weighting method and multi system coordination index model were used to scientifically evaluate the balance of employment structure through static/dynamic coordination index to ensure the comparability of analysis. Findings: The results show that the overall deviation of the employment structure of the tertiary industry shows a downward trend, but the employment ratio of key industries rises; The imbalance of age structure is aggravated and the sex ratio is stable; The urban-rural employment ratio showed a V-shaped curve. The inter provincial differentiation is significant, the static index fluctuates greatly, and the dynamic index has been improved for a long time, but its stability is insufficient, reflecting the driving characteristics of industry, population and region. Unique Contribution to Theory, Practice and Policy: Theoretically, it reveals the synergetic influence mechanism of industry population region on employment resources, and enriches the explanation of structural employment contradictions. In terms of policy, it is suggested to establish dynamic monitoring, coordinate industrial and employment policies, and implement regional differentiation. In practice, it provides guidance for government planning and enterprise manpower adjustment, alleviates the contradiction between "recruitment difficulty" and "employment difficulty", and enhances economic resilience.